Break to You - Shusterman, Neal; Young, Debra; Knowlden, Michelle (New York, NY : Quill Tree Books, an imprint of HarperCollins Publishers, 2024)
"Adriana knows that if she can manage to keep her head down for the next seven months, she might be able to get through her sentence in the Compass juvenile detention center. Thankfully, she's allowed to keep her journal, where she writes down her most private thoughts when her feelings get too big. Until the day she opens her journal and discovers that her thoughts are no longer so private. Someone has read her writings--and has written back. A boy who lives on the other side of the gender-divided detention center. A boy who sparks a fire in her to write back. Jon's story is different than Adriana's; he's already been at Compass for years and will be in the system for years to come. Still, when he reads the words Adriana writes to him, it makes him feel like the walls that hold them in have melted away"--
Keywords: Juvenile detention -- Juvenile fiction; Imprisonment -- Juvenile fiction; Juvenile detention homes -- Juvenile fiction; Diaries -- Juvenile fiction; Juvenile detention -- Fiction; Imprisonment -- Fiction; Juvenile detention homes -- Fiction; Diaries -- Fiction; Romance fiction; Fiction